Fathers' experiences of the health visiting service: A qualitative study. (2nd October 2019) - Menzies, Jennifer
Abstract : Inappropriate and ineffective care of men and fathers is a barrier to positive family care within the health visiting service. This care in relation to fathers needs to be addressed in light of changes to the social climate. The purpose of this study was to investigate the experiences fathers have of the health visiting service, the way the health visiting service is delivered and if it is targeting fathers and families effectively and equitably. The study was of a qualitative interpretive design, using a purposive sample of between five and seven fathers who regularly attended a fathers' group. A semi-structured interview to establish fathers' experiences of the health visiting service and a phenomenological approach and open coding analysis of the experiences of the fathers were used.